Prevalence and Risk Factors for COPD at High Altitude: A Large Cross-Sectional Survey of Subjects Living Between 2,100–4,700 m Above Sea Level - Guo, Yanfei; Xing, Zhenzhen; Shan, Guangliang; Janssens, Jean-Paul; Sun, Tieying; Chai, Di; Liu, Weiming; Wang, Yuxia; Ma, Yali; Tong, Yaqi; Huang, Yilin; Cao, Yang; et al. (Frontiers in Medicine, 2020)
Aim of study: 400 million people live at high altitude worldwide. Prevalence and risk factors for COPD in these populations are poorly documented. We examined the prevalence and risk factors for COPD in residents living at an altitude of 2,100 to 4,700 meters. Methods: We performed a cross-sectional survey in Xinjiang and Tibet autonomous region. A multistage stratified sampling procedure was used to select a representative population aged 15 years or older from eight high altitude regions. All participants underwent pre- and post-bronchodilator measurement of forced expiratory volumes. COPD was diagnosed according to 2019 Global Initiative for Chronic Obstructive Lung Disease (GOLD) criteria. Results: Between June, 2015 and August 2016, 4,967 subjects were included. Median age was 38.0 years (range: 15-91 years; inter-quartile range: 28-49 years); 51.4% participants were female. Overall prevalence of spirometry-defined COPD was 8.2% (95% CI 7.4–8.9%): 9.3% in male (95% CI 8.2–10.4%), and 7.1% in female (95% CI 6.1–8.2%). By multivariable logistic regression analysis, COPD was significantly associated with being aged ≥40 years (odds ratio: 2.25 [95% CI 1.72-2.95], P<0.0001), exposure to household air pollution (OR: 1.34 [95% CI 1.01-1.79], P=0.043), and a history of tuberculosis (OR: 1.79 [95% CI 1.23-2.61], P=0.030), while living at a higher altitude (OR: 0.45 [95% CI 0.33-0.61], P<0.0001) and having a higher educational level (OR: 0.64 [95% CI 0.43-0.95], P=0.025) were associated with a lower prevalence of COPD. Conclusions: Our results show that the spirometry-defined COPD is a greater health problem for residents living at high altitudes. Preventing exposure to household air pollution and reducing the incidence of tuberculosis should be public health priorities for high altitude residents.